MICROSOFT VISUAL BASIC 6.0 APPLICATION FOR BORROWING MONEY IN COOPERATION DRAFT CORPORATE HEADQUARTERS - Suherman Suherman; Drs. Sunarto Usna, MMSI (Jurnal Sistem Informasi, 2002)
With the system of borrowing money on employees of cooperatives. Gas Negara(Persero) which uses a computer service to members who will borrow money, can beimproved, all applications submitted can be processed to generate a decision and timeto generate the decision process and the time is much shorter processes.Computerization of data generated by lending money stored in the hard disk. So it ismore efficient entry and exit easy loan money in cash under control.